Thoughts On Education And Culture: An Interview With Russell And Annette Kirk - G. Daniel Harden; Mary Harden (Educational Considerations, 1992)
We must constantly remind ourselves that the true ends of education are wisdom and virtue. Self control and personal restraint are virtues that need to be nurtured in our modern culture.